Sustainable development, water resources management and women's empowerment: The Wanaraniya water project in Sri Lanka - Aladuwaka S.; Momsen J. (Gender and Development, 2010)
Water is one of the most important natural resources, and its effective management is essential given its scarcity. In rural Sri Lanka, the management of available water resources needs special attention because investment for water resource improvement is hard to obtain, and water itself is relatively scarce in the drier areas of the country. The Wanaraniya Water Project pipes water 6.5km from its source to individual houses in the village, saving women daily time and effort. The project is founded on commitments to community participation and the adoption of local knowledge. It was initiated by women, and has been operated and managed by them for the last six years. This study argues that the project can serve as a model for better planning of water management, and focuses on the unique strategies and innovative methods that have been used. In particular, it shows the impact of involvement in the project on women’s empowerment. The implementation of the project has helped women to improve their leadership qualities, confidence, self-reliance, and gain more power in the community through their successful establishment of a village water supply.
Keywords: approches et analyses; asie; cours; discipline; développement; développement participatif; environnement; géographie; histoire et politique; justice sociale; pol4022; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sri lanka; thématiques; études de genres

Care, justice et dépendance : introduction aux théories du care - Garrau, Marie; Goff, Alice Le (Presses Universitaires de France, 2010)
Ce livre retrace le parcours théorique de la notion de dépendance dans la philosophie féministe contemporaine, de la critique du fonctionnement du concept dans la rhétorique de l’État libéral aux modalités de son inclusion dans une théorie de la justice. Deux axes se dégagent, qui convergent dans une tentative de redéfinition de la notion d’autonomie : les relations de dépendance constituent le point de départ de l’éthique du « care » ou de la sollicitude, qu’il s’agira de présenter ici ; elles ont en outre suscité des reformulations importantes des théories de la justice sur la base d’une anthropologie politique qui cherche à prendre acte de la constitution relationnelle des agents moraux. L’enjeu de ces réflexions n’est donc pas simplement de réévaluer la notion de dépendance, mais aussi de fournir un fondement normatif à l’inclusion des personnes dépendantes dans la communauté morale et politique, voire d’élaborer une conception renouvelée de la citoyenneté.
Keywords: approches et analyses; autonomie; capitalisme; care; discipline; justice sociale; philosophie; politiques néolibérales; projet charge mentale; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques; théorie du care

Intimate Justice: A Critical Analysis of Sexual Satisfaction - McClelland, Sara I. (Social and Personality Psychology Compass, 2010)
This article elaborates an intimate justice framework to help guide research on sexual satisfaction. Using a critical historiography approach, I examine the etiology and development of the psychological construct of “satisfaction” over the last century and argue that social and political antecedents to satisfaction ratings are an essential and under-theorized aspect of research in this field. By examining what are considered to be the most influential definitions in life satisfaction research, I identify conceptual gaps, oversights, and disagreements that characterize this body of work, and specifically its theoretical treatment of inequity. Moving to the intimate domain, I argue that the field of sexual satisfaction must include theories and methods that systematically consider the role of social and sexual stigmas as antecedents to sexual satisfaction ratings. In the conclusion, building from existing social justice theories, I propose an intimate justice framework as a means to guide research that can highlight issues of entitlement and deservingness in sexual satisfaction research. This is particularly important as sexual satisfaction is increasingly used as an indicator of individual and relational well-being; however, this construct is presently limited and inadequately measured for women and men who experience limited sexual rights in the socio-political domain because of their gender and/or sexual minority status.
Keywords: approches et analyses; capacitisme; cours; discipline; intersectionnalité; justice sociale; premier cycle; psychologie; racisme; ressource en ligne; sciences humaines; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques

Sous les yeux de l’Occident : recherches féministes et discours coloniaux - Mohanty, Chandra Talpade (Genre, postcolonialisme et diversité de mouvements de femmes, 2010)
Note de l’éditeur Traduit de l’anglais. Texte original: Under Western eyes : Feminist scholarship and colonial discourses. In Feminism without borders : Decolonizing theory, practicing solidarity. 17-42. Durham : Duke University Press. 2003. Tous droits réservés. Reproduit avec l’aimable autorisation de l’éditeur. Parution originale 1986.
Keywords: EDI; afro-féminisme; approches et analyses; cours; discipline; discours dominant; droits des femmes*; ethnocentrisme; féminisme africain; féminisme autochtone; féminisme du sud; féminisme décolonial; féminisme transnational; histoire et politique; injustices épistémiques; inégalités; justice sociale; militance; patriarcat; phi4336; philosophie politique; pol4212; pratiques féministes; premier cycle; privilèges; racisme; sciences humaines; sociologie; sujet du féminisme; système colonial; systèmes d'oppressions; thématiques; théorie féministe; violences

Pour une meilleure compréhension des particularités de la violence familiale vécue par les femmes autochtones au Canada - Montminy, Lyse; Brassard, Renée; Jaccoud, Mylène; Harper, Elizabeth; Bousquet, Marie-Pierre; Leroux, Shanie (Nouvelles pratiques sociales, 2010)
La violence conjugale en milieu autochtone présente des particularités qui demeurent trop souvent ignorées ou confondues avec celles d’autres groupes de femmes violentées au Canada. Cet article rapporte les résultats d’une analyse de documents produits au cours des trois dernières décennies afin de dégager les principales caractéristiques de cette problématique. Cette analyse suggère que la notion de violence familiale doit être privilégiée à toute autre et que la violence conjugale dont les femmes autochtones sont victimes se distingue tant par ses formes, sa fréquence que par sa gravité.Aspects that are unique to conjugal violence as experienced by Aboriginal women are often ignored and confounded with those of other groups of abused women in Canada. This article presents an analysis of documents from different sources of knowledge that have been produced over the last three decades in order to identify distinctive dimensions of this problem. The analysis points to the significance of the notion of family violence over other terms that are used to describe conjugal violence and to the different facets of Aboriginal women’s experiences of violence with regards to prevalence, severity and forms of violence.
Keywords: amériques; analyse documentaire; approches et analyses; canada; cours; discipline; femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; travail social; trs3500; violences; violences conjugales

Geography and gender: Feminism and a feeling of justice - Wright, Melissa W. (Progress in Human Geography, 2010)
The recent emphasis on emotional geographies has turned critical attention to the connections linking affect and social justice. It is hard to imagine this ‘emotional turn’ in the field without much of the ground having been laid by feminist challenges to epistemology, objectivity, rationality, to the gendering of knowledge and the conceptualization of human embodiment, psychic life, subjectivity, and political agency, all in relation to power so often substantiated around a belief that the public and the private are discrete and oppositional domains necessary for organizing social, economic, and political life. In this report, I address the following questions. How can feminist and emotional geography tighten their connections, fuel their shared passions and generate a synergy of scholarship oriented toward activism and progressive change? How can geographies of feeling broaden the path for justice that feminism endeavors to plow? In doing so, I continue my emphasis on research that grounds theoretical discussion with research conducted in activist projects conducted in the name of social justice. I do so as a matter of my own emotional investments – I firmly believe that scholarship must engage with the ways in which people beyond the academy wrestle with the concepts in their daily lives that scholars contemplate, sharpen, and circulate through academic production. So the debates that we scholars so often have with ourselves over the finer points of theory reveal, in my view, their greater significance when they provide tools useful for people who seek to create kinder and more compassionate worlds. Thus, I highlight the scholarship that creates toolkits out of feminist scholarship, emotional geographies, and research on social justice.
Keywords: approches et analyses; care; discipline; genre; géographie; justice sociale; militance; ressource en ligne; sciences humaines; thématiques; travail; travail du care; émotions

Le genre d’une migration post-coloniale : de Meknès (Maroc) à Montréal (Québec) - Yolande Cohen (Genre & Histoire, 2010)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; afrique; afrique du nord; amériques; approches et analyses; canada; cours; discipline; ethnographie; france; his4830; histoire; histoire du féminisme; histoire et politique; immigration; justice sociale; maghreb; maroc; migration; militance; mouvements des femmes*; mouvements féministes; point de vue situé; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques